2016
DOI: 10.1007/s00436-016-5014-5
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles (Anopheles) petragnani Del Vecchio 1939—a new mosquito species for Germany

Abstract: The so far known species of the Anopheles Claviger Complex, Anopheles claviger s.s. and Anopheles petragnani, can only be distinguished by partial overlapping characteristics of immature stages and by nucleotide sequence variation of the genomic ribosomal DNA (rDNA) internal transcribed spacer 2 (ITS2) region. The known distribution of An. petragnani is so far restricted to the western Mediterranean region, whereas An. claviger s.s. occurs across most of Europe, up to the Middle East and North Africa. In our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Anopheles petragnani is another thermophilic species which predominantly occurs in southwestern Europe (Becker et al 2010). In Germany, it was first detected in 2015 (Becker et al 2016) but has since been reported from four sites in the southern half of the country, with annual larval collections at one of these sites (rock pools in the river Murg close to the city of Forbach in the federal state of Baden-Württemberg) from 2015 to 2019, indicating persistent maintenance (Kampen et al 2017;Kampen and Werner, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Anopheles petragnani is another thermophilic species which predominantly occurs in southwestern Europe (Becker et al 2010). In Germany, it was first detected in 2015 (Becker et al 2016) but has since been reported from four sites in the southern half of the country, with annual larval collections at one of these sites (rock pools in the river Murg close to the city of Forbach in the federal state of Baden-Württemberg) from 2015 to 2019, indicating persistent maintenance (Kampen et al 2017;Kampen and Werner, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…claviger is a Palearctic species that is largely distributed all over Europe, the Middle East, and North Africa. 31 It has been reported in Spain, 32 France, 33 Italy, 34 Belgium, 35 Russia, 36 Libya, 37 and so forth. In Morocco, this species is predominantly located in the mountainous regions of the country, especially at fairly high altitudes up to 1000 m, and it is totally absent from desertic regions.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike its sibling species Anopheles petragnani restricted to the Mediterranean basin, An. claviger is a Palearctic species that is largely distributed all over Europe, the Middle East, and North Africa 31 . It has been reported in Spain, 32 France, 33 Italy, 34 Belgium, 35 Russia, 36 Libya, 37 and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae were collected in artificial water reservoirs (metal wadies) in allotment gardens in Kielce. The species is a sibling species of Anopheles claviger s.s., whose morphological differentiation is only possible on the basis of subtle differences in the structure of eggs and larvae [50,51]. PCR methods are used to unambiguously distinguish these species [52].…”
Section: Current Knowledgementioning
confidence: 99%